2017
DOI: 10.3390/genes8100274
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Long Non-Coding RNAs and Coding Genes Uncovers a Complex Regulatory Network That Is Involved in Maize Seed Development

Abstract: Long non-coding RNAs (lncRNAs) have been reported to be involved in the development of maize plant. However, few focused on seed development of maize. Here, we identified 753 lncRNA candidates in maize genome from six seed samples. Similar to the mRNAs, lncRNAs showed tissue developmental stage specific and differential expression, indicating their putative role in seed development. Increasing evidence shows that crosstalk among RNAs mediated by shared microRNAs (miRNAs) represents a novel layer of gene regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…For example, Xu et al 32 constructed a ceRNA network to explain the function of lncRNAs in phosphate starvation of rice. Zhu et al 33 reported a complex ceRNA network consisting of lncRNAs, mRNAs, and miRNAs in maize seed development. A large number of circRNAs was found in the ethylene pathway of tomato, possibly acting as ceRNAs 69 .…”
Section: Proposed Model In Response To Cu Toxicity Based On Cerna Netmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Xu et al 32 constructed a ceRNA network to explain the function of lncRNAs in phosphate starvation of rice. Zhu et al 33 reported a complex ceRNA network consisting of lncRNAs, mRNAs, and miRNAs in maize seed development. A large number of circRNAs was found in the ethylene pathway of tomato, possibly acting as ceRNAs 69 .…”
Section: Proposed Model In Response To Cu Toxicity Based On Cerna Netmentioning
confidence: 99%
“…CircRNAs are a class of endogenous, covalently closed, circular RNAs generated by alternative circularization [30]. Increasing numbers of studies in animals, humans, and plants have proved that lncRNAs and circRNAs can act as competing endogenous RNAs (ceRNAs) to regulate a wide range of biological and developmental processes [31][32][33][34][35][36][37]. CeRNAs, including mRNAs, lncRNAs, circRNAs, and pseudogenes, are the transcripts that can competitive bind common miRNA response elements (MREs), and which are also named miRNA sponges to sequester specific miRNAs and suppress their function [30,31,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs show the response to external and internal stimuli [17] and have the role in the tissue development in the plants [18]. Genome-wide computational techniques are • Ahsan Z. Rizvi is with Institute of Human Genetics, CNRS, Montpellier,…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid advance of next-generation sequencing (NGS) techniques and bioinformatics tools, a large number of lncRNAs have been identified from various organisms such as animals and plants (Sun et al 2017b). However, lncRNAs have been identified in a limited number of plant species such as Arabidopsis thaliana, medicago, potato, rice, strawberry, tomato (Solanum lycopersicum), and maize (Guo & Liu 2017;Kang et al 2017;Nejat & Mantri 2017;Scarano et al 2017;Zheng et al 2017;Zhu et al 2017). Furthermore, studies revealing functional roles of identified lncRNAs in plants are rare.…”
Section: Introductionmentioning
confidence: 99%